Pergeseran Paradigma dalam Metode Penentuan Awal Bulan Hijriah di Malaysia - Qulub, Siti Tatmainul; Rochmah, Nor Afifatur (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2025)
Determining the beginning of the Hijri month is a vital aspect of Muslim religious practice in Malaysia, which has undergone a significant paradigm shift in recent decades. The traditional method of crescent moon sighting (rukyatul hilal), which relied on direct observation, has transformed into an integrated astronomical hisab method. This study aims to analyze this paradigm shift, using a qualitative approach with a literature review of books, journals, and articles related to the method of determining the beginning of the month in Malaysia. The analysis utilizes Thomas Kuhn's paradigm shift theoretical framework to understand the ongoing scientific-religious transformation. The results show that the integration of rukyat and hisab, according to the MABIMS criteria (minimum altitude of 3 degrees and elongation of 6.4 degrees), can improve the accuracy, consistency, and harmonization of the beginning of the month. However, the new paradigm faces sociocultural resistance, particularly from traditionalist groups, and challenges related to the uneven distribution of observation infrastructure. The conclusion confirms that this transformation is not merely a technical change, but a scientific-cultural revolution that requires education, dialogue between stakeholders, and religious legitimacy for the sustainable implementation of modern methods for determining the beginning of the Hijri month in Malaysia.